SIGNALL: A European Partnership Approach to Deaf Studies via New Technologies - LEESON, LORRAINE (My University, 2009)
This paper presents preliminary outcomes of a European Commission funded project which brings together industry, academics and practitioners in an innovative project to create an international forum of learning. SIGNALL II builds on the successes of SIGNALL I (a Leonardo da Vinci project). It is promoted by Interesource Group (Ireland) Limited partnered with the Centre for Deaf Studies, Trinity College Dublin (Ireland), Irish Deaf Society (Ireland), Finnish Association of the Deaf (Finland), University of Sussex (UK), the Foundation for the Promotion of Entrepreneurship, Lodz,(Poland) and Grant Advisor, Brno (Czech Republic). SIGNALL 2 aims to utilise the experience, results, partnership alliances and the relationships built up with supporters and user groups from SIGNALL I and to develop an accredited digital course on Perspectives on Deafness (POD). Accreditation leads to the transfer of credit points (under the European Credit Transfer System) amongst participating third level educational establishments promoting international mobility in education and the transparency of qualifications. Experiential and evidenced-based material will illustrate experiences of deafness by using digitized case studies and video materials. The course will be offered as a distance-learning programme with fully accessible (signed, subtitled) course content in each partner country on-line. This is essential given that Deaf people are the most under-represented group accessing third level education, for example, [17], [5], and is challenging given the linguistic diversity of the European Union. For example, signed languages differ from territory to territory, even where spoken languages are the same (i.e. Britain and Ireland have very different natural signed languages ? British Sign Language and Irish Sign Language). The core content for the `Perspectives on Deafness? course has been created by the Centre for Deaf Studies (CDS) at Trinity College Dublin. CDS has actively engaged in the development of digital learning assets to support traditional delivery of programmes, and are actively engaged in the development of blended learning diplomas and degrees. European perspectives are added, allowing for the exploration of shared ? and differing- experiences of Deafhood [14] across Europe as well as notions of d/Deafness as a medical, social, cultural, and historical construct. Human rights perspectives are also explored in this wide reaching course. This paper outlines the background to the development of this course, outlining rationale, content, creation of digital materials, the nature of international involvement and the challenges to creating a repository of digital courseware that will be accessible and relevant to Deaf and hearing students and employers across the European Union, and beyond.
INTED 2009
PRESENTED
Valencia, Spain
Keywords: E-learning; Deaf Studies; Signed Languages; Accessibility